Outage probability analysis of cooperative spatial modulation systems - Altin, Gökhan; Aygölü, Ümit; Basar, Ertugrul; Çelebi, Mehmet Ertugrul (IEEE, 2016)
The capacity analysis of the spatial modulation (SM) scheme is different than that of the multiple-input multiple-output (MIMO) systems. Since the information is conveyed not only through the M-ary constellation domain but also through the antenna domain, the capacity of SM is expressed as the sum of the capacities of these two domains. Due to this summation, the outage probability of SM differs from the conventional systems. A detailed analysis of the outage probability of SM has not been given in the literature yet. In this work, first, we derive the outage probability performance of the classical SM system and second, we extend the results to the cooperative scenarios under fixed, selective and incremental relaying techniques. It is shown that SM and cooperative SM systems provide better performance compared to conventional modulation systems in terms of outage probability.